2009
DOI: 10.1017/s0033291709991632
|View full text |Cite
|
Sign up to set email alerts
|

Reduced connectivity of the auditory cortex in patients with auditory hallucinations: a resting state functional magnetic resonance imaging study

Abstract: These data have identified a trait deficit specific to AH patients. Since this deficit was characterized within both A1 and A2 it is expected to result in the disruption of multiple auditory functions, for example, the integration of basic auditory information between hemispheres (via A1) and higher-order language processing abilities (via A2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
83
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 55 publications
14
83
1
1
Order By: Relevance
“…Gavrilescu et al, found that interhemispheric connectivity of both primary (A1) and secondary (A2) auditory cortices were decreased in schizophrenic patients with AH when compared with non-AH patients and healthy controls, whilst the latter two groups did not show any differences in functional connectivity. These findings suggest a disruption of the integration of multiple auditory functions (basic and higher order) in AH patients (Gavrilescu et al 2010). Another study group focused on a network which is composed of regions known to be involved in (inner) speech processing and verbal thought, encompassing the temporo-parietal junction (TPJ), inferior frontal gyrus (IFG) (consisting of Broca's area and the right hemisphere homotope), anterior cingulate cortex (ACC), amygdala, and insula.…”
Section: Local Network Analyses and Progress In Understanding Neuropsmentioning
confidence: 77%
“…Gavrilescu et al, found that interhemispheric connectivity of both primary (A1) and secondary (A2) auditory cortices were decreased in schizophrenic patients with AH when compared with non-AH patients and healthy controls, whilst the latter two groups did not show any differences in functional connectivity. These findings suggest a disruption of the integration of multiple auditory functions (basic and higher order) in AH patients (Gavrilescu et al 2010). Another study group focused on a network which is composed of regions known to be involved in (inner) speech processing and verbal thought, encompassing the temporo-parietal junction (TPJ), inferior frontal gyrus (IFG) (consisting of Broca's area and the right hemisphere homotope), anterior cingulate cortex (ACC), amygdala, and insula.…”
Section: Local Network Analyses and Progress In Understanding Neuropsmentioning
confidence: 77%
“…The results suggested that the deficits seen in the hallucinating patient group compared to normal controls may be essentially the same as those seen in the non-hallucinating patients, but that they may be more severe (McKay et al, 2000). Additionally, Gavrilescu et al (2010) have recently published functional MRI evidence of reduced interhemispheric connectivity of primary and secondary auditory cortices in schizophrenia patients who experience auditory hallucinations compared to both non-hallucinating patients and normal controls. Non-hallucinating patients did not show a reduction in connectivity relative to normal control participants, demonstrating a trait effect apparently specific to hallucinators.…”
Section: Introductionmentioning
confidence: 89%
“…Most interestingly, some findings of dysconnectivity are associated with symptoms. For example, SZ patients with a history of auditory hallucinations have significantly reduced interhemispheric connectivity in primary and secondary auditory cortices when compared with SZ patients without auditory hallucinations and healthy controls [45]. When using a bilateral amygdala seed, Hoptman et al [46] reveal reductions in connectivity between amygdala and ventral prefrontal cortex regions in patients with SZ or schizoaffective disorder.…”
Section: Dysconnectivity Of Sz Indentified By Seed-based Analysismentioning
confidence: 99%